Перспективи розвитку екологічного підприємництва в Україні - Желібо, Євген Петрович; Гацька, Людмила Павлівна; Мурована, Тетяна Олександрівна (Ефективна економіка, 2020)
У статті проаналізовано необхідність (глобальні тренди і національні переваги) та можливості (наявний потенціал) для інтенсивного розвитку екологічного підприємництва в Україні. Розглянуто такі перспективні напрямки, як екологізація системи управління підприємств і організацій шляхом формування корпоративної системи екологічного менеджменту та сертифікації її за стандартом ISO14001; екологізація процесу виробництва шляхом запровадження технологій ресуроефективного і більш чистого виробництва; формування ланцюгів поставок і перехід до циркулярної економіки, зокрема – шляхом використання біологічних промислових відходів як сировини для альтернативної енергетики; управління поводженням з відходами (роздільний збір, переробка та вторинне використання, сучасні методи утилізації відходів); виробництво екологічних товарів/послуг, в першу чергу – органічного сільського господарства. Доведено, що у вітчизняному органічному підприємництві надзвичайно великою є роль малого та середнього бізнесу, а виробництво органічної продукції має суттєвий потенціал для розвитку та займає лідируючі позиції серед інших напрямків екологізації підприємницької діяльності. Стверджується, що темпи поширення екологічного підприємництва в Україні стримує недосконала правова база, відсутність фінансування та механізмів підтримки і стимулювання підприємців. Зроблено висновок, що розвиток екологічного підприємництва має беззаперечні переваги, орієнтований на економічну стабільність, є стратегічним завданням для України і може розраховувати на суттєву підтримку європейського співтовариства та міжнародних організацій.

This article analyzes the necessity (global trends and national advantages) and the opportunities (available potential) for the intensive development of environmental entrepreneurship in Ukraine. The following perspective directions are reviewed: greening of the management system of enterprises and organizations through the formation of the corporate environmental management system and its certification according to the ISO14001 standard; greening of the production process through the introduction of technologies of resource-effective and cleaner production; the formation of supply chains and the transition to a circular economy, in particular through the use of biological industrial wastes as raw materials for alternative energy; waste management (separate collection, recycling, modern waste management methods); production of ecological goods / services, first of all - organic agriculture. It is proved that the role of small and medium-sized businesses is extremely important in domestic organic entrepreneurship, and the production of organic products has significant potential for development and occupies a leading position among other areas of greening entrepreneurial activity. In particular, Ukraine ranks first in the Eastern European region in terms of organic arable land. It is argued that the pace of eco-entrepreneurship in Ukraine is hampered by an imperfect legal framework, lack of funding and mechanisms to support and encourage entrepreneurs. It is determined that in order to overcome the constraints it is necessary to coordinate the interaction of all subjects of environmental activity, their consolidation on the formation of the national system of development of environmental entrepreneurship, the development of a strategy for innovative development of environmental entrepreneurship in Ukraine in the context of globalization challenges. It is concluded that the development of environmental entrepreneurship has undeniable advantages, is oriented towards economic stability, is a strategic task for Ukraine and can count on the significant support of the European community and international organizations.
Keywords: екологічне підприємництво; «зелений» бізнес; екологічні товари; ресурсоефективне і більш чисте виробництво; органічне сільське господарство; циркулярна економіка; environmental entrepreneurship; Green business; environmental goods; resource efficient and cleaner production; organic farming; circular economy